Tantangan Yang Dihadapi UMKM Kecil: Bantuan Fasilitas Permodalan Pedagang Kaki Lima Kelurahan Siranindi Kota Palu - Nandita Fradina; Lutfiani; Andita Triana; Rahdiyatul Zahra; Hj Suasa; Dandan Haryono; Nurhayati Hamid (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
UMKM are an important pillar in the Indonesian economy, including in Palu City. One of the most common types of UMKM in Palu City is street vendors, which play an important role in providing goods and services at affordable prices to the community. However, despite their large contribution, street vendors often face various challenges, especially in terms of access to capital facilities. This study aims to identify the challenges and constraints faced by street vendors in Palu City in accessing capital facilities provided by the government and other financial institutions. The method used was a qualitative approach with a case study, involving in-depth interviews with two street vendors. Street vendors face several major obstacles, such as unfamiliarity with application procedures, low levels of financial literacy, and conditions that are considered burdensome. This study recommends that the government and financial institutions simplify application procedures, improve socialization programs, and provide assistance for street vendors to facilitate access to existing capital facilities.